2014
DOI: 10.1002/cyto.a.22612
|View full text |Cite
|
Sign up to set email alerts
|

Simple computational technique to quantify nuclear shape asymmetry

Abstract: The nucleus of an eukaryotic cell is a membrane-bound organelle containing a major part of the cellular genome. Nuclear shape is controlled by forces generated in the cytoskeleton, nuclear envelope and matrix of the nucleus and may change when the balance of these forces is disturbed. In certain cases, such changes may be indicative of cell pathology. Nuclear shape feature is being commonly addressed in both experimental research and diagnostics; nevertheless its symmetry-related aspects receive little attenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…The nuclei of cervical squamous epithelial cells are nearly spherical, which change to oblate spheroidal due to cells flattening during smear preparation. Under microscope, nuclei appear to have near circular profile (that is, round or oval) [ 18 ]. Alteration in nuclear shape is either due to changes in the nuclear lamina or by forces from the cytoplasm [ 28 , 29 ].…”
Section: 0 Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The nuclei of cervical squamous epithelial cells are nearly spherical, which change to oblate spheroidal due to cells flattening during smear preparation. Under microscope, nuclei appear to have near circular profile (that is, round or oval) [ 18 ]. Alteration in nuclear shape is either due to changes in the nuclear lamina or by forces from the cytoplasm [ 28 , 29 ].…”
Section: 0 Discussionmentioning
confidence: 99%
“…Statistical analysis was performed to seek any significant differences among the three diagnostic classes. Studies have reported various methods of nuclear shape evaluation [ 18 – 22 ]. Performance of the proposed techniques was compared with three techniques of nuclear shape evaluation in the literature, namely, radial asymmetric (RA) [ 18 ], shape factor (SF) [ 18 ], and rim difference (RD) [ 23 ].…”
Section: 0 Introductionmentioning
confidence: 99%
See 3 more Smart Citations